The impact of dance on fitness: Physical and educational benefits for high school students - Tekla Fruzsina TÓTH; Puskás Andrea LENTÉNÉ (GeoSport for Society)
Dancing, similarly to all sports, requires excellent stamina and mobility. It improves physical performance, sense of rhythm, mental and psychological development, and shapes personality. Our research examined dance's effect on high school students' fitness status. Our goal was to explore the role of dance education within school frameworks in developing individual abilities and skills. Therefore, we examined the effect of school dance programs on fitness and compared the outcome with the results of students who only participated in daily physical education classes. Furthermore, we studied the effect of folk dance on the performance of students who have dance and physical education classes at school. During our research, we carried out the NETFIT (National Uniform Student Fitness Test) test, as well as an online survey at three schools: Ferenc Medgyessy Grammar School and Vocational Technical School in Debrecen, at Nyíregyháza Art Vocational High School and Esze Tamás Grammar School in Mátészalka. The students of these schools participated in three different exercise programs. The members of the first group had dance classes only, the students of the second group took part in physical education classes besides dancing, and those in the third group did not participate in any form of dance movement at school. The research results show that dance, besides its influence on personality development, has a beneficial effect on fitness and is essential in creating a healthy lifestyle. The outcome of the tests proves that students who, in addition to physical education, participate in a dance exercise program reach significantly higher performance and fitness levels. The results also highlight that many students participating in the dance program choose some kind of sports activity outside school as a hobby.